Universidade aberta do Brasil: percursos e discursos na institucionalização de um sistema público de educação a distância - Pimentel, Marijane Alves Andrade (2015)
The study investigated the Open University of Brazil (UAB) and its institutionalization as a Public System of Distance Education. The thesis points out that UAB is configured as a network of organized complex systems, since each system that makes up this network has elements that are interrelated paradoxically, of autonomous and interdependent, from their differences. Thus, the constitution of a system can not do without the assumption of wholeness and organization so that the elements that compose it are considered from their interrelations. Guided in a qualitative research, adopting the systemic perspective, with the instruments to literature review, document analysis and an online form, and a field of study, through the virtual pages of educational institutions linked to the UAB System. It was based on the concepts of systems based on the contributions of Ludwig von Bertalanffy (2010); Maturana and Varela (1995); Luhmann (2009); Edgar Morin (1977) and Frijot Capra (2010). Sought on the theories and systemic concepts, indicators and characteristic elements of a system, to the light of those analyze the UAB system in their organization and structure.